Information gaps : a group perspective on the management of heart failure : a thesis presented in partial requirements [sic] for the degree of Master of Philosophy, Massey University - Reed, Susan (Massey University, 2000)
Heart failure is a complex condition that incurs considerable socio-economic burden, and poor prognosis. Careful management of the syndrome is required if a patient is to have a reasonable quality of life. Health professionals generally acknowledge that there is a need to improve care of patients with heart failure and that there are treatment gaps between the recommended therapies, and the care patients are actually receiving. This pilot study used the grounded theory approach to discover the main concerns, and how they are continually resolved, of a group that manage heart failure. It is argued that information gaps are present in the management of heart failure. It was demonstrated that when there is an absence of a cohesive group, occurring under conditions of changing funding structures within the context of boundaries merging, it is often necessary to alert others. The alerting of others is how the group continually resolve the information gaps. However, when people are not alerted, are left out of the loop, poor symptom management is more likely to occur, and information gaps are perpetuated. The loop in this study is comprised of information relating to heart failure and the members who both send and receive it. Indeed, if the loop is able to be activated so that people are in the loop information is shared and the chances for better heart failure management are more likely. The impact of effective heart failure management for the patients means that although heart failure as a chronic disease is limiting, it is still possible in many cases, to improve quality of life and longevity. The findings of this study also suggest that there is a need for nurses as health professionals to move towards ways to reduce information gaps and improve access to information, and it is suggested that case management and information systems are the ways to do so.
Keywords: Heart failure; Heart failure patients; Patient education; Patient rehabilitation